Political discussion on WhatsApp groups among IIUM students - Wan Mohd Ghazali, Wan Norshira; Sedu, Nerawi; ,; , (2018)
The study aims to explore the usage of WHatsApp among young Malaysian voters in discussing Malaysian issues or topic. It is also conducted to investigate the kinds of political and related issues discussed by the members of the created WhatsApp groups. In the context of the recent Malaysia General Election (GE 14), held on 9 May 2018, WhatsApp was seen by political observers and media practitioners as an attractive virtual gathering place for some Malaysians to express and share their opinions and observations of MAlaysian politics. This study wis exploratory and experimental in nature which employed virtual focus group, with two different groups of respondents, assigned to two different WhatsApp groups, i.e. control group and experimental group. The discussions among the members of both groups were monitored from 23rd April 2018 until 10 May 2018.